Pendidikan Islam di Pondok Pesantren Waria Al-Fatah Yogyakarta dalam Mengembangkan Religious Practice - Asyhar, Ahmad Zainul (Program Studi Pendidikan Guru Madrasah Ibtidaiyah STAI Senori Tuban, 2024)
This research discusses the analysis and effectiveness of Islamic education at the Waria Al-Fatah Yogyakarta Islamic Boarding School in developing religious practices for its students. This Islamic boarding school is unique because it serves the transgender community by offering valuable insights regarding inclusivity in Islamic education. This approach integrates forms of religious values ​​and gender identity. This Islamic boarding school always strives to create an environment conducive to fostering positive spirituality and comprehensive learning. This study uses a type of qualitative research with a phenomenological approach. Data collection was carried out descriptively regarding religious education, followed by data interpretation by carrying out investigations. This was done to determine whether or not the structure and relationships between the data were sharp. The research results show that the Waria Al-Fatah Islamic Boarding School emphasizes moderate and tolerant religious teaching with various additional programs, including counseling guidance and social activities to support the development of religious practice. These findings prove that Islamic education can also be adapted to meet the special needs of marginalized groups, while still maintaining the essence of religious teachings. Hopefully, this research can become a reference for developing inclusive and humanistic education models in the future.